2002
DOI: 10.1097/00124784-200211000-00006
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Knowledge and Attitudes in Chinese Medical Professionals and Students before and after an Informational Lecture on HIV/AIDS

Abstract: The rapid increase in human immunodeficiency virus (HIV) prevalence and incidence requires that Chinese health professionals mobilize for HIV prevention. The article describes an HIV/acquired immune deficiency syndrome knowledge and attitude assessment administered before and after a lecture. HIV transmission knowledge was good, with 90 percent to 100 percent of participants correctly identifying means of transmission. Prior to and after the lecture, 43 percent and 21 percent, respectively, were unwilling to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 6 publications
2
22
0
1
Order By: Relevance
“…These negative attitudes are similar to those of Chinese medical professionals and students, who were unwilling to sit or work with an HIV-infected person (Buskin, Li, Yin, Yu & McGough, 2002). Negative attitudes towards HIV-infected colleagues were also noted in previous studies in Nigeria, in which 43.6% of the HCWs studied were uncomfortable being assisted by an infected colleague, and 51.1% were uncomfortable sharing a bathroom with an infected colleague (Aisien & Shobowale, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…These negative attitudes are similar to those of Chinese medical professionals and students, who were unwilling to sit or work with an HIV-infected person (Buskin, Li, Yin, Yu & McGough, 2002). Negative attitudes towards HIV-infected colleagues were also noted in previous studies in Nigeria, in which 43.6% of the HCWs studied were uncomfortable being assisted by an infected colleague, and 51.1% were uncomfortable sharing a bathroom with an infected colleague (Aisien & Shobowale, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…men, and sex workers (Buskin, Li, Yin, Yu, & McGough, 2002;Feng, 2002;Li, Cole, Zhang, & Chen, 1993;Li, Wu, Zhao, Lin, Detels, & Wu, in press;Wu, Qi, Zeng, & Detels, 1999). Consequently, the control of the HIV/AIDS epidemic in China has been significantly hindered.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that an HIV/AIDS stigma reduction intervention for service providers could increase knowledge and awareness of the disease and change attitudes by reducing fear of HIV transmission through everyday contact and increasing level of comfort, confidence, motivation, and willingness to provide care to PLWHA (Buskin et al, 2002;Lalonde et al, 2002;Rutstein et al, 1998;Sowell, Seals, Wilson, & Robinson, 1998). These studies also highlighted the high importance of training service providers in working with HIV/ AIDS and of incorporating HIV/AIDS intervention activities into their routine activities (Buskin et al, 2002;Wu et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In China, Buskin et al 2002 reported that prior to health education lecture, 10% of participants believed that HCW could be selective in adherence to safety precautions but this attitude improved to 4% after lectures.…”
Section: B-phcws Risk For Acquiring Bbipsmentioning
confidence: 99%